El cine documental hecho por mujeres como instrumento de denuncia y visibilización de los feminicidios sexuales y las desapariciones de mujeres en Ciudad Juárez (México) - Dr. Javier JUÁREZ (Fonseca, Journal of Communication, 2023)
The article analyzes documentary films made by female filmmakers about the episodes of systematic sexual femicides and disappearances of women in Ciudad Juárez (Mexico). Through the study of the main works developed by female filmmakers, the transformative and denouncing capacity of documentary film is addressed, applying the gender perspective in its analysis in a transversal way.